2017
DOI: 10.20344/amp.8003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Foley Catheter Balloon for Cervix Priming in Term Pregnancy

Abstract: Introduction: Foley catheter promotes cervix priming by a direct mechanical effect of distension.Material and Methods: A prospective observational study was conducted at a tertiary hospital, including all cases of induction of labor with Foley catheter between September 1, 2013 and November 30, 2015. Women were eligible if they had a singleton pregnancy with a Bishop score < 6 and a gestational age ≥ 41 weeks or a medical indication for induction of labor. The primary outcome was the Bishop score variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…2,3,16,18,20 One possible reason for this achievement may be the policy adopted by the Department of using Foley catheter as a mechanical method for cervical priming and labor induction in women with one previous uterine scar which allows vaginal births with no documented increase on maternal or neonatal morbidity. 24 The number of deliveries in this group has increased over time, reflecting the number of primary CSs and of > 1 previous CS performed in the past. 17,22 Since in Portugal women may choose the public maternity where they want to deliver, it is possible that the knowledge of the lower CS rate in our institution and particularly in this group might have had influence on this choice.…”
Section: Discussionmentioning
confidence: 96%
“…2,3,16,18,20 One possible reason for this achievement may be the policy adopted by the Department of using Foley catheter as a mechanical method for cervical priming and labor induction in women with one previous uterine scar which allows vaginal births with no documented increase on maternal or neonatal morbidity. 24 The number of deliveries in this group has increased over time, reflecting the number of primary CSs and of > 1 previous CS performed in the past. 17,22 Since in Portugal women may choose the public maternity where they want to deliver, it is possible that the knowledge of the lower CS rate in our institution and particularly in this group might have had influence on this choice.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that single balloon catheter can cause reproductive tract infection after insertion; thus, strict aseptic operation is imperative ( 9 ). A recent study has confirmed that the effect of cervical single balloon expansion in promoting cervical ripening is relatively better, and it can effectively shorten the stage of labor and improve the natural delivery rate with high safety ( 10 ). Cervical expansion of a single balloon catheter has a higher natural labor rate and lower delivery rate of cesarean section than that of the double balloon catheter, rendering the former more suitable for clinically promoting cervical ripening ( 11 ).…”
Section: Discussionmentioning
confidence: 97%
“…In the past, transcervical Foley catheter was replaced by pharmacological agents, but recently it has showed promising results, either alone or in combination with other methods, especially when used with unfavorable Bishop scores. [17][18][19] Oxytocin is a commonly used method for IL worldwide, either alone or in combination with other methods. However, when used alone, it is less effective than intravaginal prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, transcervical Foley catheter was replaced by pharmacological agents, but recently it has showed promising results, either alone or in combination with other methods, especially when used with unfavorable Bishop scores. 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation